IFAT BRASIL 2024 - BRASIL, IFAT (Revista Brasileira de Meio Ambiente & Sustentabilidade, 2024)
Link de direcionamento para Anúncio: <a href="https://abrir.link/pyLVJ" target="_blank" rel="noopener" data-saferedirecturl="https://www.google.com/url?q=https://abrir.link/pyLVJ&source=gmail&ust=1710899582616000&usg=AOvVaw3FizBgzGdUbmFsvAEGRNGz">https://abrir.link/pyLVJ